2019
DOI: 10.1097/dss.0000000000001859
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Injections for Masseter Reduction in East Asians

Abstract: BACKGROUND Cultural ideals for a slimmer face have led to an upsurge in interest in facial contouring among East Asians. Although surgical resection has traditionally been the main treatment option, botulinum toxin injection is becoming a popular, noninvasive alternative. OBJECTIVE To describe the use of botulinum toxin injection for masseter reduction in East Asians. METHODS An electronic search of the PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…Usually 100 units of BoNT‐A was diluted with 2 or 2.5 ml of saline to obtain a concentration of 50 or 40 U/ml, and 40–60 U and 0.8–1.5 ml of BoNT‐A was injected into either side of the masseter muscle 11,17–20 . Despite various multi‐point injection methods are commonly performed, 1 there are physicians who still prefer single‐point injection, 21 and some claim that there is no difference between the effects of single‐point injection and multi‐point injection 22 . In this cadaver study, we found that the upward ICG spread in 94.4% of masseters that injected with 1 ml of ICG exceeded the mouth corner‐tragus line.…”
Section: Discussionmentioning
confidence: 99%
“…Usually 100 units of BoNT‐A was diluted with 2 or 2.5 ml of saline to obtain a concentration of 50 or 40 U/ml, and 40–60 U and 0.8–1.5 ml of BoNT‐A was injected into either side of the masseter muscle 11,17–20 . Despite various multi‐point injection methods are commonly performed, 1 there are physicians who still prefer single‐point injection, 21 and some claim that there is no difference between the effects of single‐point injection and multi‐point injection 22 . In this cadaver study, we found that the upward ICG spread in 94.4% of masseters that injected with 1 ml of ICG exceeded the mouth corner‐tragus line.…”
Section: Discussionmentioning
confidence: 99%
“…Botulinum toxin A (BTA) injection has been considered as a favorable procedure in treating benign masseteric hypertrophy because of its effective reduction of the volume of masseter muscle and with no significant side effects [6]. In fact, BTA injection in the extraocular muscles has also been suggested to provide temporary relief of diplopia in selected patients during the active phase of TAO.…”
Section: Introductionmentioning
confidence: 99%
“…Botulinum toxin type A (BoNT-A) was first used for weakening the eye muscles, and its application was expanded by Moore and Wood in 1994 as a treatment for masseter hypertrophy [ 1 , 2 , 3 ]. The demand for BoNT-A injections into the masseter muscle is increasing markedly, especially among some Asian populations in which it is assumed that the ovoid facial shape and slim lower face is optimal [ 3 , 4 , 5 ]. These injections are used not only for aesthetic purposes to reduce masseter hypertrophy, but also for therapeutic purposes to reduce bruxism and clenching [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%